2021
DOI: 10.3390/nu13082556
|View full text |Cite
|
Sign up to set email alerts
|

Oat and Barley in the Food Supply and Use of Beta Glucan Health Claims

Abstract: Beta glucan is a type of soluble dietary fibre found in oats and barley with known cholesterol-lowering benefits. Many countries globally have an approved beta glucan health claim related to lowering blood cholesterol, an important biomarker for cardiovascular disease. However, the use of these claims has not been examined. The aim of this study was to explore the range and variety of oat and barley products in the Australian and global market within a defined range of grain food and beverage categories and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…There are commercially available methods for D-Glucose assay. One of these D-Glucose assay method is by using the two enzymes of glucose oxidase, and peroxidase [34]. This method is preferred for its sensitivity, and is based on the enzyme glucose oxidase that oxidize D-Glucose into gluconic acid and hydrogen peroxide (H 2 O 2 ).…”
Section: β-Glucans Assay Methodsmentioning
confidence: 99%
“…There are commercially available methods for D-Glucose assay. One of these D-Glucose assay method is by using the two enzymes of glucose oxidase, and peroxidase [34]. This method is preferred for its sensitivity, and is based on the enzyme glucose oxidase that oxidize D-Glucose into gluconic acid and hydrogen peroxide (H 2 O 2 ).…”
Section: β-Glucans Assay Methodsmentioning
confidence: 99%
“…Commercially, barley is already used in a range of products. A recent survey sampling 2462 products from the four main supermarkets in metropolitan Sydney showed that 13.4% of breakfast cereals, 14.3% of breads and 0.8%–3.0% of savoury biscuits, grain-based muesli bars, flour and plant-based milk alternatives contained whole grain barley, while this ingredient was absent from the sampled noodles/pasta ( Hughes and Grafenauer, 2021 ). In addition, BARLEYmax®, a whole grain barley line high in beta-glucan and resistant starch developed by CSIRO, was present in a few samples (0.4%–2.4%) of breakfast cereals, bread and grain-based muesli bars.…”
Section: Barley Foodmentioning
confidence: 99%
“…The colours of barley cultivars and landraces are associated with the accumulation of flavonoid pigments in the pericarp and aleurone layer of the seed. Barley grains are a rich source of beta-glucans, which offer numerous benefits to human health globally ( Hughes and Grafenauer, 2021 ). Some cultivars can provide resistant starch to help control obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o resíduo de mosturação é rico em fibras alimentares, destacando-se as fibras prebióticas β-glucanas e arabinoxilo-oligossacarídeos, e compostos fenólicos, como por exemplo o ácido ferúlico. No entanto, este resíduo possui alto teor de umidade (70 a 75 %) (Hughes & Grafenauer, 2021;Shih et al, 2020).…”
unclassified